Angiogenesis within atherosclerotic plaques: Mechanical regulation, molecular mechanism and clinical diagnosis - Hanxiao Chen; Chengxiu Peng; Fei Fang; Yuhao Li; Xiaran Liu; Ying Hu; Guixue Wang; Xiaoheng Liu; Yang Shen (Mechanobiology in Medicine)
Atherosclerosis (AS) is a disease characterized by focal cholesterol accumulation and insoluble inflammation in arterial intima, leading to the formation of an atherosclerotic plaque consisting of lipids, cells, and fibrous matrix. The presence of plaque can restrict or obstruct blood flow, resulting in arterial stenosis and local mechanical microenvironment changes including flow shear stress, vascular matrix stiffness, and plaque structural stress. Neovascularization within the atherosclerotic plaque plays a crucial role in both plaque growth and destabilization, potentially leading to plaque rupture and fatal embolism. However, the exact interactions between neovessels and plaque remain unclear. In this review, we provide a comprehensive analysis of the origin of intraplaque neovessels, the contributing factors, underlying molecular mechanisms, and associated signaling pathways. We specifically emphasize the role of mechanical factors contributing to angiogenesis in atherosclerotic plaques. Additionally, we summarize the imaging techniques and therapeutic strategies for intraplaque neovessels to enhance our understanding of this field.